2021
DOI: 10.1093/mnras/stab1358
|View full text |Cite
|
Sign up to set email alerts
|

The cosmology dependence of galaxy clustering and lensing from a hybrid N-body–perturbation theory model

Abstract: We implement a model for the two-point statistics of biased tracers that combines dark matter dynamics from N-body simulations with an analytic Lagrangian bias expansion. Using Aemulus, a suite of N-body simulations built for emulation of cosmological observables, we emulate the cosmology dependence of these nonlinear spectra from redshifts z = 0 to z = 2. We quantify the accuracy of our emulation procedure, which is sub-per cent at k = 1 hMpc−1 for the redshifts probed by upcoming surveys and improves at high… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
119
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 71 publications
(124 citation statements)
references
References 107 publications
5
119
0
Order By: Relevance
“…The value of 𝑏 𝑠 2 changes by ∼ 13% between the two. Kokron et al (2021) found that the tracer-tracer and tracermatter spectra are least sensitive to varying 𝑏 𝑠 2 . It is therefore the hardest to constrain with only these statistics, as evidenced by the simulated likelihood analyses carried out therein.…”
Section: Best-fit To 𝑘Nn-cdfs and Range Of Scales Of Validitymentioning
confidence: 93%
See 4 more Smart Citations
“…The value of 𝑏 𝑠 2 changes by ∼ 13% between the two. Kokron et al (2021) found that the tracer-tracer and tracermatter spectra are least sensitive to varying 𝑏 𝑠 2 . It is therefore the hardest to constrain with only these statistics, as evidenced by the simulated likelihood analyses carried out therein.…”
Section: Best-fit To 𝑘Nn-cdfs and Range Of Scales Of Validitymentioning
confidence: 93%
“…This spectrum is orders of magnitude smaller than other basis spectra at all scales (see fig. 1 of Kokron et al 2021).…”
Section: Best-fit To 𝑘Nn-cdfs and Range Of Scales Of Validitymentioning
confidence: 98%
See 3 more Smart Citations